Relationship Between Lower Extremity Strength Asymmetry And Jump And Sprint Performance - Celil Kaçoğlu (Türk Spor ve Egzersiz Dergisi)
The relationship between inter-limb strength asymmetry and athletic performance is not clearly well-known. Different results in the literature makes it difficult to form a common consensus on this issue. The aim of this study was to investigate the relationship between inter-lower limb strength asymmetry (ILLSA) values and jump and sprint performances. Forty-eight individuals (21.5±2.8 years, 1.74±0.1 m, 67.3±9.7 kg) voluntarily participated in this study. All participants participated in squat (SJ), countermovement jump (CMJ), 40m sprint run tests and right and left isokinetic concentric knee flexion and extension strength (IS) test at low (60°.s-1) and high (300°.s-1) angular velocities. The symmetry angle formula was used in order to determine the isokinetic knee strength asymmetry values between inter-lower limb. According to the results it was revealed that there was no relation (p gt;0.05) between ILSSA at low and high angular velocities and squat jump (r = -0.106 ̶ 0.200), countermovement jump (r = -0.11 ̶ 0.087) and 40m sprint (r = 0.012 ̶ 0.810) performance. In conclusion, there is no negative or positive relationship between inter limb isokinetic knee strength symmetry angle and jump and sprint performances in physically active individuals.